Calculation of the Ductility Factor (m) of Composite Columns Using Experimental Results and Finite Element Software - Jafari , Seyyed shahram; Tavousi Tafreshi, Shahriar (Management Strategies and Engineering Sciences, 2025)
This study investigates the deformation capacity factor (m) of composite columns using experimental data and finite element numerical modeling. The real behavior of these columns was analyzed using the Krawinkler–Ibarra cyclic loading protocol, and parameters such as deformation capacity, modified axial resistance, and hysteretic behavior were assessed to evaluate energy absorption ability. The research combines numerical analyses in finite element software and experimental results from concrete-filled steel tube (CFT) columns. Force-displacement curves under cyclic loading were extracted, and by identifying key points on the curve (yield, maximum, and failure points), the deformation capacity factor (m) was calculated according to the FEMA 356 guidelines and the Iranian code (publication 360). The results showed that the m factor for CFT sections ranges from 1.4 to 5.6, while for SRC sections, it ranges from 1.0 to 4.0. At axial loads exceeding 50% and 65% of the nominal capacity, respectively, the behavior of CFT and SRC sections shifts from deformation-controlled to force-controlled. Additionally, an empirical relationship for predicting axial load capacity was developed, improving the accuracy of predictions compared to common models. The findings indicate that CFT composite columns exhibit significant deformation capacity, and their m factor exceeds the values recommended in codes in most cases. This study contributes to a better understanding of the nonlinear behavior of composite columns and the optimization of seismic design, especially for retrofit projects.